From Moral Authority to Policy Integration: The Role of Religious Leaders in Marital Mediation in Indonesia and Malaysia - Musleh Harry; Tutik Hamidah; Jundiani Jundiani; Muhammad Nasrulloh; Rafeah Saidon (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
Divorce rates in certain Southeast Asian countries remain a growing concern, with some regions experiencing one divorce in every four marriages. Formal mediation in religious courts has proven largely ineffective in mitigating this trend. However, two Muslim-majority regions, namely Rembang in Indonesia and Melaka in Malaysia, consistently demonstrate significantly lower divorce rates. This study seeks to explore the underlying factors contributing to this pattern. Employing a qualitative comparative method, this empirical research investigates how religious leadership contributes to family conflict resolution in both communities. The study involved interviews with six (6) informants in Indonesia and six (6) in Malaysia. The findings reveal that the presence of a strong religious ecosystem, in which religious leaders act as informal mediators, plays a central role in preventing divorce and promoting reconciliation. In these communities, religious figures such as imams or kiai are widely respected and trusted, and are often consulted before legal proceedings are considered. In Malaysia, the role of religious leaders has been institutionalised through state-supported programs that integrate them into official family protection and dispute resolution mechanisms. In contrast, Indonesia has not yet developed formal policies that support the role of religious leaders in marital mediation, despite their substantial influence in rural and coastal communities. This study concludes that religious leaders function not only as moral authorities but also as effective mediators who connect community values with personal disputes. Strengthening collaboration between religious institutions and state authorities is crucial to enhancing non-litigation divorce prevention strategies. The integration of faith-based mediation into public policy could significantly contribute to sustaining family resilience in Southeast Asian Muslim societies.Keywords: religious authority; mediation; divorce; marriage.